Rh single-atom nanozymes for efficient ascorbic acid oxidation and detection - Shi, Xiaoyue; Li, Juan; Xiong, Yu; Liu, Ziyu; Zhan, Jinhua; Cai, Bin (Nanoscale, 2023)
The management of ascorbic acid (AA) in biological fluids is of significant importance for body functions and human health, yet challenging due to the lack of high-performance sensing catalysts. Herein, we report the design of Rh single-atom nanozymes (Rh SAzymes) by mimicking the active sites of ascorbate peroxidase toward efficient electrocatalytic oxidation and detection of AA. Benefiting from the enzyme-mimicking single-atom coordination, the Rh SAzyme exhibits an unprecedented electrocatalytic activity for AA oxidation with an onset potential as low as 0.02 V ( vs. Ag/AgCl). Combined with the screen-printing technology, a miniaturized Rh SAzyme biosensor was firstly constructed for tracking dynamic trends of AA in the human subject and detecting AA content in nutritional products. The as-prepared biosensor exhibits excellent detection performances with a wide linear range of 10.0 μM-53.1 mM, a low detection limit of 0.26 μM, and a long stability of 28 days. This work opens a door for the design of artificial single-atom electrocatalysts to mimic natural enzymes and their subsequent application in biosensors. Rh single-atom nanozymes are designed to mimic the active sites of ascorbate peroxidase, based on which electrochemical sensors have been developed for efficient ascorbic acid detection.